Analisis Perbandingan Pendidikan Agama Islam Di Indonesia Dan Thailand: Studi Faktor-Faktor Penghambat Penyebaran Islam Di Thailand - Monica, Sofia; Dompak, Timbul; Salsabila, Lubna (Prosiding, 2024)
This study examines the comparison of Islamic religious education in Indonesia and Thailand and the factors influencing the spread of Islam in both countries. Indonesia, with the largest Muslim population in the world, has a well-structured Islamic education system supported by various institutions such as pesantren (Islamic boarding schools), madrasahs, and Islamic schools. Strong government support and widespread accessibility to education have accelerated the spread of Islam in Indonesia. In contrast, in Thailand, where the majority of the population is Buddhist, Islamic education is concentrated in the southern provinces such as Pattani, Yala, and Narathiwat. Despite some policies aimed at integrating Islamic education into the national education system, their implementation is often ineffective and limited by financial support and social stigma against the Muslim community. The study's findings indicate that government policy support, accessibility of educational institutions, and societal response are key factors influencing the spread of Islam. This research provides recommendations to strengthen Islamic religious education in Thailand, including increased government support, expanded accessibility to Islamic educational institutions, and efforts to reduce social stigma. These findings are expected to contribute significantly to the field of religious and educational studies and serve as a basis for more effective policies in supporting Islamic education in Southeast Asia.